Positive Effect of Surface Doping with Au on the Stability of Pt-Based Electrocatalysts - Gatalo, Matija; Jovanovic, Primoz; Polymeros, George; Grote, Jan-Philipp; Pavlisic, Andraz; Ruiz-Zepeda, Francisco; Selih, Vid Simon; Sala, Martin; Hocevar, Samo; Bele, Marjan; Mayrhofer, Karl; Hodnik, Nejc; et al. (ACS Catalysis, 2016)
Corrosion resistance of a transition-metal-rich PtCu3/C oxygen reduction reaction (ORR) catalyst as a representative of Pt alloy-based materials has been significantly improved by doping with small amounts of gold (<1 at. %). Transmission electron microscopy imaging shows near-surface segregation of both platinum and gold with the underlying core consisting predominantly of intermetallic PtCu3. The resulting PtAu skin catalyst shows improved resistance against Cu dissolution, as well as against carbon corrosion if compared to its PtCu3 precursor. Also, it exhibits a much higher Pt and carbon stability than a widely used Pt/C standard. Most importantly, the Au doped sample shows a substantial improvement in stability at the elevated temperature (60 degrees C) degradation test (10 000 cycles; 0.4-1.2 Vim) simulating a real PEM fuel cell environment.
Keywords: platinum; alloy; electrocatalyst; corrosion; Au doping